Ethics management in the public service a sensory-based strategy - Ireni Saban, Liza; Berdugo, Galit (Routledge critical studies in public management, 2017)
Ethics Management in the Public Service offers a new perspective for ethics management in the Public Administration. The traditional approaches, relying on codified rules, regulations, and guidelines, have not yielded the results expected of them and have not managed to serve as an effective tool in the hands of public administrators struggling with ethical and moral questions. Unlike Code-based training strategies, focusing on the written word and its application in real-life situations, the authors introduce a sensory-based strategy to sharpen public administrators' senses. This type of training would first aim to help the public administrators become conscious of the use of their senses in a routine manner, not necessarily limited to ethical issues. Once an individual becomes more conscious of his or her acts and thinking process, they can better understand their motives, and again attempt to modify their conduct if and when necessary. This book holds that sensory-based metaphors are an important device in applying the hermeneutic approach to ethics management in the public service, as they can enhance new understandings about the extent to which particular ethical principles might be disabling. Using metaphors as a management tool of public service ethics helps to communicate public values and ethical guidelines to public administrators.